2022
DOI: 10.1163/22941932-bja10082
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the intensity of heartwood formation in Scots pine (Pinus sylvestris L.) ontogenesis

Abstract: Summary An essential stage in woody plant ontogeny (heartwood (HW) formation) determines tree resistance to weather conditions, wood quality (moisture, colour, resistance to biodegradation), and regulates the proportion of functionally active sapwood (SW) in the total trunk biomass. In this study, the patterns of HW formation depending on tree age and cambial age within the same tree were studied in the North-West of Russia in Scots pine in a lingonberry pine forest. It is shown that HW either repeats the trun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Quantitative differences in the activity of these enzymes can serve as a marker of more intensive formation and/or consumption of certain substances of a carbohydrate and phenolic nature, a different balance of which is maintained both during PCD and during heartwood formation. Previous studies have shown that the rate of HW formation in Pinus sylvestris depends on the cambium age [24].…”
Section: Introductionmentioning
confidence: 94%
“…Quantitative differences in the activity of these enzymes can serve as a marker of more intensive formation and/or consumption of certain substances of a carbohydrate and phenolic nature, a different balance of which is maintained both during PCD and during heartwood formation. Previous studies have shown that the rate of HW formation in Pinus sylvestris depends on the cambium age [24].…”
Section: Introductionmentioning
confidence: 94%
“…We selected objects in the same-aged lingonberry pine forests for the study, common in the northern and middle taiga. We established sample plots in May 2021, as we described it earlier [ 77 ]. The pine age line was represented by three groups: (1) 30 years (Plot 4)—the beginning of the vegetative–reproductive ontogenesis stage; (2) 70–80 years (Plots 9, 1)—the middle of the vegetative–reproductive ontogenesis stage, as well as the age at which the wood quality was a significant indicator, since pine stands were assigned for felling following forestry requirements in this period; (3) 170–180 years (Plot 3)—the age at the end of the vegetative-reproductive stage of ontogenesis and the beginning of the extinction stage of tree growth ( Figure S4a ).…”
Section: Methodsmentioning
confidence: 99%
“…We carried out a continuous count of trees in 2 cm steps of diameter on the sample plots. The following stand characteristics were determined: tree species composition, density, the sum of cross-sectional areas (basal area per hectare), average diameter and height, and growing stock [ 77 ]. Three (Plot 9), four (Plot 1), and five (Plots 4, 3) model trees were selected on the sample plot.…”
Section: Methodsmentioning
confidence: 99%
“…We found a very high correlation degree between cambial age and the number of heartwood rings. Therefore, heartwood formation is inextricably linked with cambial aging [14,15].…”
Section: Introductionmentioning
confidence: 99%